Konfigurasi Makna Postingan Duta Wisata Uda Uni Kota Padang Pada Akun @Adwindopadang Dalam Membangun Citra Diri - maisya, salsa ratu; Sary, Marisa Puspita; Sutjipto, Vera Wijayanti; Safitri, Dini; Putri, K. Y.S.; Romli, Nada Arina (Universitas Islam Negeri Imam Bonjol Padang, 2024)
Social media, particularly Instagram, is used for communication and sharing activities through photos and videos. Additionally, this platform serves to shape self-image and respond to various commnets. For example is @adwindopadang, a group of youth touris ambassadors (Uda Uni Kota Padang) who act as stakeholders in the tourism sector. This research aims to analyze how @adwindopadang builds their self-image through Instagram. The study employs Ferdinand de Saussure’s semiotic theory to understand the meaning construction from the photos and texts posted by the @adwindopadang Instagram. It uses a constructivist paradigm with a qualitative descriptive approach. The data examined includes the photos and descriptions on the account. The research findings indicate that @adwindopadang construct self-image through a combination of verbal and non-verbal messages, reflected in the captions, photography, style, distinctive fashion choices. The conclusion drawn is that the self-image built by @adwindopadang displays characteristics of simplicity, intelligence, humility, modernity, fasion-forwardness, and inspiration, successfully creating a positive image on social media